Development of a new approach to evaluate buffalo welfare, the Ruminant Welfare® project - Domenico, Vecchio; Tamaio, Juan Esteban; Luigi, Bertocchi; Esterina, De Carlo (Revista Colombiana de Ciencias Pecuarias, 2017)
Animal welfare is a growing, compelling and urgent topic because of the interest that it generates among the citizens and consumers. The goal to be fulfilled is to define systems and protocols for assessing animal welfare that should be impartial, reproducible and science-based on risk analysis. On these premises, the Italian Ministry of Health has signed an agreement with the IZSLER, through the CReNBA and IZSM through the CReNBuf on development and management of a system to evaluation of welfare and biosecurity in buffaloes breeding system. The checklist development was based on the Risk Assessment Methodology as suggested by EFSA. Building on the CReNBA’s work developed on the welfare dairy cow, this method is based on the analysis of two data groups: The assessment of the hazards (non-ABMs) occurring as a result of environmental conditions; the assessment of the risks, with the concerned adverse effects (ABMs), run by animals living in those environments. The system developed consists in 83 observations, listed in a multiple-choice checklist divided in five macro-areas: Farm management and personnel, Facilities and equipment, Animal based measures, Biosecurity and Alarm systems. The result of each area also provides an indication of the burden and importance of each of these on the final calculation of the animal welfare value. These checks represent a functional and smart instrument to allow assign a numerical animal welfare index to each farm. In addition, by the data collected in each area, to supply at the Veterinarians and breeders the tools to improve farm management and structures, respecting the farm’s sustainability, and is preparatory to given to the development of a Ministerial trademark for animal welfare, giving answers to consumers and add value to the correct activities of the farmers.